Donepezil Derivatives Targeting Amyloid-β Cascade in Alzheimer's Disease - Mezeiová, Eva; Chalupova, Katarina; Nepovimova, Eugenie; Gorecki, Lukas; Prchal, Lukas; Malinak, David; Kuca, Kamil; Soukup, Ondrej; Korabecny, Jan (Current Alzheimer research, 2019)
Alzheimer's Disease (AD) is a neurodegenerative disorder with an increasing impact on society. Because currently available therapy has only a short-term effect, a huge number of novel compounds are developed every year exploiting knowledge of the various aspects of AD pathophysiology. To better address the pathological complexity of AD, one of the most extensively pursued strategies by medicinal chemists is based on Multi-target-directed Ligands (MTDLs). Donepezil is one of the currently approved drugs for AD therapy acting as an acetylcholinesterase inhibitor. In this review, we have made an extensive literature survey focusing on donepezil-derived MTDL hybrids primarily targeting on different levels cholinesterases and amyloid beta (Aβ) peptide. The targeting includes direct interaction of the compounds with Aβ, AChE-induced Aβ aggregation, inhibition of BACE-1 enzyme, and modulation of biometal balance thus impeding Aβ assembly.
Keywords: donepezil; Donepezil; Animals; Alzheimerova nemoc; Protein Aggregation, Pathological; Acetylcholinesterase; lidé; amyloidní beta-protein; zvířata; cholinesterasové inhibitory; Cholinesterase Inhibitors; Amyloid beta-Peptides; acetylcholinesterasa; patologická konformace proteinů; Alzheimer Disease; Humans